Application of AI to Create Dynamic Video Lessons Supporting Japanese Language Teaching - Nguyễn Thị Út Duyên (Journal of Technical Education Science, 2025)
As the demand for learning Japanese continues to rise, integrating advanced technology into language education has become an inevitable trend. This study explores the application of Artificial Intelligence (AI) in generating scenario-based video simulations to enhance learners’ communication skills through an engaging and interactive learning environment. The research employs a combination of literature review, pedagogical experiments, student surveys, and content analysis to evaluate the effectiveness of this approach compared to traditional teaching methods. The video system follows a structured process, including AI-generated visuals, motion synthesis, text-to-speech conversion, and content integration. AI tools utilized in this study include ChatGPT, TTSFree, Hailuo AI, CapCut, and other supporting platforms. Experimental results at Ho Chi Minh City University of Technology and Education indicate that AI-powered video-based instruction significantly enhances learner engagement (98.4%) and improves vocabulary retention, grammar acquisition, and communication reflexes. Notably, 75% of students reported increased confidence in Japanese communication compared to traditional methods. The findings reinforce the role of AI in education and highlight its potential for broader application, paving the way for innovative foreign language instruction in the era of Education 5.0.